A new genus and new species of Tarsonemidae (Acari: Heterostigmata) from the Brazilian rainforests - Lofego, Antonio C. [UNESP]; Pitton, Thafarel [UNESP]; Rezende, José M. [UNESP] (Systematic and Applied Acarology Society, 2016)
Ochoanemus dux gen. nov., sp. nov. (Tarsonemidae: Tarsoneminae) is described from adult males and females collected on leaves of Psidium cattleyanum Sabine (Myrtaceae) from the Atlantic Forest in coastal area of São Paulo State, Brazil. Measurements and illustrations of both sexes are provided. This species is unusual in the shape of dorsal setae d (on males and females), sc1 (males) and v1 (females) which are club-shaped and serrate.
Keywords: Acari; Mites; Phytonemus; Tarsonemoidea; Tarsonemus; Taxonomy